2003
DOI: 10.1038/oby.2003.52
|View full text |Cite
|
Sign up to set email alerts
|

High Dietary Calcium Reduces Body Fat Content, Digestibility of Fat, and Serum Vitamin D in Rats

Abstract: PAPAKONSTANTINOU, EMILIA, WILLIAM P. FLATT, PETER J. HUTH, AND RUTH B.S. HARRIS. High dietary calcium reduces body fat content, digestibility of fat, and serum vitamin D in rats. Obes Res. 2003;11:387-394. Objective: This study investigated which aspect of energy balance was responsible for the decrease in body fat content of rats fed a high-calcium, high-dairy protein diet. Research Methods and Procedures: Male Wistar rats were fed a control diet (25% kcal fat, 14% kcal protein from casein, 0.4% by weight cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
4
9

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(116 citation statements)
references
References 24 publications
5
98
4
9
Order By: Relevance
“…In agreement with the results from our study, they were able to show quite a substantial increase in fecal fat and energy excretion and no significant difference in EE. 6 To our knowledge, no other studies in humans have tested the effect of calcium from dairy products on fecal fat excretion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the results from our study, they were able to show quite a substantial increase in fecal fat and energy excretion and no significant difference in EE. 6 To our knowledge, no other studies in humans have tested the effect of calcium from dairy products on fecal fat excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have found inverse associations between calcium intake and body weight. [1][2][3][4][5][6] In their analysis of data from NHANES III, Zemel et al 2 observed an inverse association between relative risk of obesity and calcium intake. Similar observations have been reported by others.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their inhibition of phosphodiesterase, methylxanthines are also antagonists of the inhibitory effect of adenosine on NE release (Dulloo et al, 1994). Finally, there is some evidence to suggest that high calcium intake produces weight loss in humans and rodents (Zemel et al, 2000;Zemel, 2002;Papakonstantinou et al, 2003;Parrikh & Yanovski, 2003). The mode of action may be through a decrease in the intracellular Ca 2 þ levels in adipocytes, followed by a decrease in lipogenic gene expression and activity, thereby promoting lipolysis (Zemel et al, 2000;Zemel, 2002;Parrikh & Yanovski, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al 12 found that mice expressing agouti protein in white fat lost more weight during food restriction on a high calcium than a low calcium diet and that the loss was exaggerated if some of the calcium came from nonfat dry milk rather than calcium salts. We reported that high levels of dietary calcium caused a small inhibition of weight gain in ad libitum fed rats 13 whereas Zhang and Tordoff 14 found no effect of dietary calcium on weight gain or adiposity of ad libitum fed mice.…”
mentioning
confidence: 83%
“…[17][18] Parikh and Yanovski 19 calculated that an extra 2000 mg calcium/day in a 2500 kcal/ day diet would bind enough lipid to account for a body weight loss of about 0.5 kg per year, which is equivalent to the weight difference that has been attributed to dietary calcium intake in the analysis by Davies et al 9 Similarly, increased fecal excretion of lipid accounted for all of the difference in body fat content of rats fed a high-calcium diet. 13 The impact of increased calcium intake during food restriction has not been evaluated but, theoretically, it could produce a proportionally greater energy deficit in low-calorie, low-fat diets.…”
mentioning
confidence: 99%